Temporal Variation in Vegetation Indexes for Pine and Beech Stands During the Vegetation Season, Szczecin Lowland, Poland - Piekarski, Paweł; Zwoliński, Zbigniew (Quaestiones Geographicae, 2014)
Located in north-western Poland, the Bukowska Forest and Goleniowska Forest are vast woodlands consisting of areas with a homogeneous species composition that have been scarcely affected by humans. In this respect, they provided an excellent subject for scientific research, the purpose of which was to determine quantitative differences in selected vegetation indices of pine and beech stands in various periods during their vegetation seasons. Another purpose was to characterize the variation in these indices for each stand in its vegetation season. Four Landsat 5 TM images taken in 2007 and 2010 at four different points of vegetation season provided the basis for the analysis. In the analysis, 19 wooded areas with a homogeneous species composition were tested. In Bukowska Forest, the tested area was a beech stand, and in Goleniowska Forest, it was a pine stand. Acquired data was used to calculate the following vegetation indices: Normalized Difference Vegetation Index (NDVI), Transformed Vegetation Index (TVI), Green Normalized Difference Vegetation Index (Green NDVI), Normalized Difference Greenness Index (NDGI) and Normalized Difference Index (NDI). Subsequent research allowed to establish that the beech and pine stands differed significantly with respect to their calculated vegetation indices. These differences derived both from the biochemical and structural attributes of leaves and needles, as well as from transformations that occur in the stands during vegetation seasons. Analysis of the indices’ allowed us to determine these differences and the influence of the stands’ phenological phases on the indices.